Correção do posicionamento de descontinuidades em procedimentos de inspeção ultrassônica Phased Array em altas temperaturas - Slongo, Juliano Scholz (2022)
Ultrasonic inspection techniques and non-destructive tests are widely applied in the evaluation products and equipment in industries such as oil, petrochemical, steel, naval, and energy. These methods are well established and efficient for inspection procedures at room temperature. However, some errors can be observed in positioning the identified flaws or discontinuities when applying such techniques in inspection procedures under high working temperatures. In such conditions, some components of the ultrasonic inspection system might be subject to temperature gradients. The presence of such gradients, in the wedge, for example, results in acoustic properties variation for adjacent regions along the medium, which can results in variation in the propagation speed of the ultrasonic wave and change the propagation of the sonic beam. Failure to consider such distortions in ultrasonic signals can result, in extreme situations, in mistaken decision-making by inspectors and professionals responsible for guaranteeing product quality or the integrity of the evaluated equipment. In this scenario, the present work develops an ultrasonic phased array inspection technique that considers the existence of temperature gradients along the path covered by the ultrasonic when applied to hot metallic surfaces. As a result, the proposed approach allows for the identification and characterization of flaws or discontinuities with good reliability. For such technique development, it is necessary to model the heat propagation process through the wedge and define the observed temperature gradients. Also, the relationship between the ultrasonic wave propagation speed and the medium temperature is experimentally evaluated. Based on the information obtained by modeling, simulation, and experimentation, the methods based on ray tracing are applied to define the ultrasonic beam path inside a non-homogeneous temperature wedge. Thus, the compensation for distortions and the reduction in the errors of flaw positioning is carried out by adequately calculating the relative excitation times for the active elements of the phased array transducer.